Bank and finance company credit officers' information needs and sources - Pung, Jones Teck Huat. (2009)
The profession in financial institutions that is responsible for approving credit applications is known generically as Credit Officers or sometimes Credit Analysts. This dissertation intends to find out more about Credit Officers from the perspectives of their information needs and the sources they use. The purpose and relevance of the information for their lending decisions is also discussed. The information needs and sources pertain to lending to business borrowers.